2022
DOI: 10.3389/fsoc.2021.780740
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Work–Family Conflicts in Germany: Risks and Chances Across Gender and Parenthood

Abstract: The COVID-19 pandemic has dramatically affected everyone’s daily life in one way or another, requiring a re-negotiation of existing strategies for work–life integration, not only for individuals but also within families and partnerships. To contribute to existing knowledge on work-life integration during COVID-19 in Germany, we look at gender and parenthood differences in the experiences of work-to-family (WFC) and family-to-work (FWC) conflicts. By accounting for employees’ previous conflict experiences, we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…The COVID-19 pandemic also changed the overall work organization and arrangements, accelerating and disrupting various trends in the work area [ 17 ]. In particular, many schools and workplaces were closed during the lockdown, so stationary work was changed to remote online, and working parents were forced to divide their time between caring for children and teleworking [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Experts assumed the transition to telework was one of the essential issues for occupational health during the COVID-19 pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 pandemic also changed the overall work organization and arrangements, accelerating and disrupting various trends in the work area [ 17 ]. In particular, many schools and workplaces were closed during the lockdown, so stationary work was changed to remote online, and working parents were forced to divide their time between caring for children and teleworking [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Experts assumed the transition to telework was one of the essential issues for occupational health during the COVID-19 pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous literature [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], we assume that changes in lifestyle during the COVID-19 pandemic were stressful events that contributed to the work-family imbalance, leading to high WFC and FWC [ 16 ]. We will examine the differences in WFC, FWC, well-being dimensions, and time pressure across countries, genders, relationship status, parenthood experience, caring for children under 12, and type of work (stationary vs. remote).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this development, we have identified three sets of determinants as potential resources and stressors for the mental health of women with young children during the first wave of the COVID-19 pandemic that also emerged in above-cited research: the work domain, psychosocial resources, and partnership and family-related aspects. 23 , 28 33 …”
Section: Introductionmentioning
confidence: 99%
“…Because subway workers had to continue working during the pandemic, for preventive purposes, they had to work under additional restrictions on personal contact and quarantine, which could have undermined their fulfilment of family responsibilities. It has been shown that work-family conflict generally increased during the COVID-19 pandemic [ 12 ]. A survey revealed that 92% of frontline nurses showed “little concern” for their families amid the pandemic [ 13 ].…”
Section: Introductionmentioning
confidence: 99%